Análise da variação termo-higrométrica e das ilhas de calor em Cuiabá – MT - Chegury, Juliana Queiroz Borges de Magalhães (2019)
The continuous urban expansion in the last decades emphasizes the importance of carrying out studies inherent to the urban climate, especially in cities with a hot climate, such as Cuiabá-MT. In this way, the present research has as general objective to analyze the thermo-hygrometric variation and the urban heat islands in Cuiabá-MT. For that, the methodology of nocturnal mobile transects was used in a period of one year, from November 2017 to October 2018. Data from the INMET official automatic station and those collected through mobile measurements, using a temperature and relative humidity datalogger, positioned on the side of a motor vehicle, protected by an alternative PVC jacket. Sixteen fixed points were defined, passing through neighborhoods of the western and northern regions of Cuiabá. It was verified that the form of occupation of the urban soil, associated with the removal of the vegetation cover are determining factors in the modification of the thermo-hygrometric behavior in the study area. As for the urban heat islands and freshness islands, there was a predominance of the occurrence of weak and moderate magnitude urban and intraurban heat islands, with differences of 0.10°C (IUHI) at 3.65°C (UHI), in the spring, autumn and winter. Strong magnitudes were observed in autumn and winter ranging from 4.2°C (UHI) to 4.85°C (IUHI). Freshness islands were identified in summer and with higher intensity in winter (-0.53°C). Urban Freshness islands were identified in summer and with higher intensity in winter (-0.53°C). Therefore, with the results of this research, the microclimatic variations existing in the city of Cuiabá and, especially, in the expansion areas, can be considered both in the incentive of new research and in the guidance of public planners and managers in urban interventions.